Waste Bank Chatbot Technology - Surya, Desayu Eka; Azzahra, F A K; Lestari, C S; Assyifa, S; Oktafiani, Dina; Maemunah, Siti (International Journal of Research and Applied Technology (INJURATECH), 2023)
Indonesia became one of the most waste- producing countries globally and was not denied, including countries that are less capable of managing the rest of the life. At the same time, management efforts with the waste bank have been sought. Therefore, we will conduct a repair analysis of the waste bank working system with Trashy Technology chatbot. This research used a literature study method by which we will manage the data from the sources of published literacy. With this technology, it is hoped that Indonesia will be able to streamline performance on the waste bank's working system so that this effort will make an established establishment that has a significant impact on waste management.